Purification and Characterization of Colophony Extracted of Pinus elliottii (Engelm, var. elliottii) - Jamille de Souza Correa; Rafaella Ribeiro dos Santos; Fauze Jacó Anaissi (Orbital: The Electronic Journal of Chemistry, 2018)
This study reports the purification and characterization of the colophony. The method involves the step of water washing and solubilization of the extracted resin of Pinus elliottii Emgelm, elliottii variety on ethanol to the filtration for removal of solid residues (sand, leaves, pieces of the branch, etc.). After purification, the colophony and turpentine were separated using a soxhlet extractor. The thermal decomposition of colophony was investigated using thermogravimetric analysis-differential thermogravimetric-differential scanning calorimetry (TG-DTG-DSC). The resin was also characterized using the technique of infrared spectroscopy (ATR-FTIR). The TG curves revealed three decomposition steps, in which a total degradation occurred after 500 °C, indicating a good thermic stability. The FTIR spectrum showed bands in 1694 cm-1, (stretch C=O) and 3362 cm-1 (stretch O-H) indicating the presence of carboxylic acid, have also been found bands corresponding to the aromatic ring. The presence of resinous acids can be confirmed.DOI: http://dx.doi.org/10.17807/orbital.v10i3.1100